Light, Conventional and Environmental Scanning Electron Microscopy of the Trichomes of Cucurbita pepo subsp. pepo var. styriaca and Histochemistry of Glandular Secretory Products - KOLB, DAGMAR (Ann Bot, 2004)
• Background and Aims In the present study, the differences between glandular and non-glandular trichomes, the secretory process and the method of secretion were studied. Previous studies on leaves of Styrian oil pumpkin (Cucurbia pepo var. styriaca) plants have shown that four morphologically and ontogenetically independent glandular and non-glandular trichome types and one bristle hair type can be distinguished. The four types of trichomes can be categorized into three glandular trichome types: type I, a short-stalked trichome with four head cells including a ‘middle-cell’, two stalk cells and one basal cell; type II, a long-stalked trichome with two head cells, a ‘neck-cell’ region and a long stalk area; type IV, a ‘stipitate-capitate’ trichome with a mesophyll cell basement, a short stalk and a multicellular head; type III, a non-glandular ‘columnar-digit’ trichome, which consists of two head cells continuous with three-celled stalk, and the basal cell. • Methods The histochemical studies (the main classes of metabolite in secreted material of glandular trichomes) were conducted in fresh and fixed hand sections, using the following tests: Sudan black B, Nile blue A, osmium tetroxide, neutral red, Naturstoffreagent A, FSA (fuchsin–safranin–astra blue), NADI (naphthol + dimethylparaphenylenediamine) and ruthenium red. Each suggested differences in the intercalations during the ontogenetical development of each trichome during the development stage. • Key Results The histochemical reactions revealed the main components of the materials secreted by all types of trichomes, which include lipids, flavones and terpenes and the different cell wall compositions. Glandular secretions were observed during environmental scanning electron microscopy (ESEM) and the trichomes compared with those seen by conventional scanning electron microscopy (CSEM). • Conclusions Scanning electron microscopy and histochemical analysis demonstrated that each of the trichomes studied produced and released secretory products in a characteristic way.